Rhubarb attenuates blood-brain barrier disruption via increased zonula occludens-1 expression in a rat model of intracerebral hemorrhage - WANG, YANG (Exp Ther Med, 2016)
Blood-brain barrier (BBB) disruption is a key pathophysiological factor of intracerebral hemorrhage (ICH). The level of zonula occludens-1 (ZO-1) has been closely associated with the degree of BBB damage, and is an indicator of BBB destruction. The aim of the present study was to evaluate the effects of rhubarb on BBB function in a rat model of ICH. ICH was induced in rats by treatment with type VII collagenase. Sham-operated rats were administered with an equal volume of saline. Following the administration of rhubarb decoction (20 g/kg), neurobehavioral function evaluation and Evans blue extravasation assays were performed at days 1, 3 and 5 after ICH. ZO-1 expression in the brain of ICH-induced rats were analyzed via reverse transcription-polymerase chain reaction (RT-PCR) and immunohistochemical analyses. The results suggested that rhubarb significantly ameliorated neurological symptoms and attenuated BBB permeability. The results of immunohistochemistry and RT-PCR studies indicated that the expression of ZO-1 expression was robust in the sham-operated group and was weak in the vehicle-treated group at day 3. The present data indicated that rhubarb effectively attenuated ICH-induced BBB damage in rats, raising the possibility that rhubarb or its active components may be considered useful as neuroprotective drugs for ICH. The protective mechanisms appeared to involve the preservation of BBB integrity and elevation of ZO-1 protein expression levels.